CHARACTERISTICS OF WAFA METHOD WITH REWARD IN LEARNING TAHFIDZ AL-QUR'AN STUDENTS AT SMP IT INSAN MANDIRI CENDEKIA PALEMBANG - Rama Satria; Abdur Razzaq; Yuniar (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to analyze the application of the Wafa method by providing rewards in learning tahfidz Al-Qur'an at SMP IT Insan Mandiri Cendekia Palembang. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that the Wafa method is applied through the Quantum Teaching model with the TANDUR (Grow, Natural, Natural, Demonstrate, Repeat, Celebrate) approach. The obstacles faced include the adaptation of new students who are not familiar with the Wafa method, limited parental involvement, inequality in teacher competence, lack of teacher training at the tasnif level, and not optimal time management. The results of the study show that the Wafa method has a positive impact on improving the quality of student memorization, especially in the memorization of Juz 30 and other juz. This method increases student motivation, discipline, and responsibility. Rewarding support and involvement of teachers and parents is essential. The Wafa method is worthy of being maintained and developed as an effective tahfidz learning strategy.